Plan de mejora para un servicio de calidad en atención al cliente en el restaurante turístico "El Mochica de Doña Fresia" distrito Huanchaco - 2018 - Gonzalez Gamboa, Carlos Eduardo (2018)
The present research has been carry out to propose an improvement plan that allows a customer quality service in the tourist restaurant "El Mochica de Doña Fresia" in the Huanchaco District. The problem formulated for the investigation was Will an improvement plan allow a quality service in customer service at the tourist restaurant "El Mochica de Doña Fresia" Huanchaco District - 2018? It was propose as a hypothesis: An improvement plan based on a diagnosis will allow a quality service in customer service at the tourist restaurant "El Mochica de Doña Fresia". Huanchaco District - 2018. The sample according to the study was made up of 65 diners who go to the tourist restaurant "El Mochica de Doña Fresia" in Huanchaco District. The research design used was nonexperimental transversal descriptive and the methods were hypothetical - deductive, analysis - synthesis and inductive - deductive method. It was obtained as a result that the surveyed clients are totally agree that an improvement plan will contribute to provide a better quality service in customer service. On the other hand, regarding the answers about the satisfaction degree with the service received, the majority was favourable, however, a small percentage that was indifferent and dissatisfied, which encourages improvement. These results were the basis for recommending actions that allow optimizing the quality of service provided in order to improve the small errors that may be witness during the process. The conclusion reached was that it was determined that an improvement plan will contribute to providing a quality service, being the majority of respondents fully agreeing; when implemented, the customer's response will be favourable to the service received, achieving a differentiation compared to other existing alternatives in the market.